الغير في منازعات عقود التجارة الإلكترونية - دربال، ياسمين Derbal, Yasmin; حسني، محمد إدريسي (عبدالالاه المحبوب, 2023)
تعد التجارة الإلكترونية من أكثر المجالات استجابة للتقدم التكنولوجي، وأوسعها استخداما لبرامج التقنيات الحديثة في معاملاتها، سواء بطرقها الذاتية العادية مرتكزة في ذلك على وسائل الاتصال بالإنترنت أو بطرقها الآلية الافتراضية، لاسيما على مستوى التعاقد التجاري الإلكتروني من خلال تعدد أطرافه، إذ يبقى الغير من بين أحد الأطراف المتدخلة في هذه العلاقة التعاقدية الإلكترونية التي تبرم عبر الوسائط الإلكترونية عن بعد مما تمتاز به من مردودية واختصار للوقت والتكاليف سواء من خلال مركزه التعاقدي من جهة أو من خلال دوره في النزاعات الحاصلة عن هذه المعاملات من جهة أخرى. Electronic commerce is considered one of the most responsive areas to technological progress, and the most widely used of modern technologies programs in its transactions, whether in its own normal ways based on means of Internet communication or in its virtual automated ways, especially at the level of electronic commercial contracting through the multiplicity of its parties, which led to third parties remaining Between one of the parties involved in this electronic contractual relationship concluded through electronic media remotely, which is characterized by its cost-effectiveness and shortening of time and costs, whether through its contractual position on the one hand, or through its role in the disputes arising from these transactions on the other hand.
Keywords: التقنيات الحديثة -- المعاملات القانونية -- العقود التجارية -- التحكيم الإلكتروني